2021
DOI: 10.1016/j.cattod.2020.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic production of H2 is a multi-criteria optimization problem: Case study of RuS2/TiO2

Abstract: Many parameters influence the photocatalytic production of H 2. Identifying and quantifying them is necessary for correct comparison of photocatalysts and right understanding of involved mechanism. In this work, we studied the photocatalytic dehydrogenation of isopropanol with titania-supported ruthenium disulfide. We studied the influence of seven parameters on the photocatalytic activity: the temperature, the composition of the reactive mixture, the mass of the photocatalyst, the flux and the energy of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 92 publications
(138 reference statements)
1
1
0
Order By: Relevance
“…It is indicated that in addition to the enhanced hydrogen desorption, the increased temperature mainly contributes to the reduction of the free energy barrier of water dissociation. From the results given in Figure c, it can be known that the β-SiC-50@PPCN allows for thermocatalytic water splitting to produce hydrogen at a suitable elevated temperature, which is consistent with previous study , and the experimental results in Figure S17. Therefore, the core–shell β-SiC-50@PPCN heterojunction not only inhibits photocarrier recombination but also remarkably promotes photo-thermo catalytic hydrogen production by reducing the energy barrier of water dissociation with respect to the increased temperature.…”
Section: Resultssupporting
confidence: 91%
“…It is indicated that in addition to the enhanced hydrogen desorption, the increased temperature mainly contributes to the reduction of the free energy barrier of water dissociation. From the results given in Figure c, it can be known that the β-SiC-50@PPCN allows for thermocatalytic water splitting to produce hydrogen at a suitable elevated temperature, which is consistent with previous study , and the experimental results in Figure S17. Therefore, the core–shell β-SiC-50@PPCN heterojunction not only inhibits photocarrier recombination but also remarkably promotes photo-thermo catalytic hydrogen production by reducing the energy barrier of water dissociation with respect to the increased temperature.…”
Section: Resultssupporting
confidence: 91%
“…43 For instance, Maheu et al compounded RuS 2 and TiO 2 to obtain RuS 2 /TiO 2 and its photocatalytic activity gradually enhanced with increasing RuS 2 content. 44 The obtained photocatalyst combining RuS 2 and CN has broad application prospects in realizing water splitting and biorefinery. Herein, a hydrothermal-calcination strategy was adopted to anchor RuS 2 nanoparticles onto CN to obtain RuS 2 @CN.…”
Section: Introductionmentioning
confidence: 99%